The Effect of Situational Leadership Style on Employee Performance with Work Motivation as A Variable Intervening in PT PLN (Persero) Service Unit Bukit Barisan Customers - Simbara, Harry; Farida Ferine, Kiki; Isa Indrawan, Muhammad (Lafadz Jaya Publisher, 2025)
This study aims to analyze the influence of situational leadership style on employee performance with work motivation as a mediating variable. The research was conducted at PT PLN (Persero) Service Unit Bukit Barisan with a total of 60 respondents. A quantitative approach was applied, and data were analyzed using SmartPLS 3. The results indicate that situational leadership style does not have a direct significant effect on employee performance, but it has a positive and significant effect on work motivation. Furthermore, work motivation has a positive and significant effect on employee performance. Another finding reveals that work motivation fully mediates the relationship between situational leadership style and employee performance. These findings emphasize the importance of leadership style in shaping employee motivation, which in turn affects performance improvement. Therefore, organizations should adopt a flexible leadership approach that focuses on enhancing employee motivation to achieve optimal performance outcomes.